The effects of urbanization on human-viper conflicts and the natural history and impacts of removal operations for Protobothrops mucrosquamatus in Northeast Taiwan - Mao, Jean-Jay; Fang, Sui-Chuan; Liu, Li-Xhan (Frontiers in Amphibian and Reptile Science, 2025)
Taiwan is a densely populated and developed island known for its industrial activities. A significant concern is the Taiwanese Habu (Protobothrops mucrosquamatus), a venomous snake that has increasingly conflicted with humans in the Lanyang Plain in northeast Taiwan. This rise in conflict is mainly attributed to urban expansion and the loss of agricultural land. From 2011 to 2015, research was conducted in collaboration with the local government and 16 fire stations responsible for managing human-snake interactions. The study focused on two primary objectives: first, to assess the effects of urbanization on human-viper conflict, and second, to analyze the characteristics of conflict sites in the Lanyang Plain while studying the natural history of P. mucrosquamatus near human settlements. Additionally, the research evaluated the impact of viper removal operations conducted by the fire stations. The findings revealed that the number of conflict cases and the dynamics of P. mucrosquamatus are increasing annually, particularly in highly urbanized, moderately urbanized, and low urbanized areas, correlating with land development activities. Conflicts have intensified across 10 districts, spreading from the town center to a 1,000-meter buffer zone in highly urbanized regions (n=2). In districts with medium to low urbanization (n=8), conflicts decreased within a 500- to 750-meter buffer zone around the town center, linked to Lanyang Plain’s population density. The primary factor contributing to disputes between residents and vipers is related to landscape features along the urbanization gradient, especially the proportion of intermediate green spaces. Principal Component Analysis (PCA) identified that the presence of buildings and transportation infrastructure is the leading landscape factor influencing the frequency of conflict events between P. mucrosquamatus and residents. This suggests that the development of such infrastructure significantly impacts the occurrence of these conflicts. The annual mortality rate of vipers handled or transported by firefighters can be as high as 11.03 ± 2.63% (mean ± SD, n=5). This study will also describe the natural history of P. mucrosquamatus, covering aspects such as reproduction, fecundity, diet, and parasite infection rates. The diet and prey of P. mucrosquamatus reflect the characteristics of urban environments and provide ecosystem services for residents.